Optimasi Identitas dan Branding Produk Unggulan melalui Inovasi Teknologi Digital di Desa Cibungur Sumedang - Wiryawan, Muhamad Ryzki; Andani, Riva (Ma'soem University, 2025)
Amid the tides of globalization and rapid digitalization, Micro, Small, and Medium Enterprises (MSMEs) in rural areas face serious challenges in preserving local identity while remaining competitive in an increasingly homogenized market. The urgency of this research lies in the pressing need to develop branding strategies that not only strengthen local cultural uniqueness but also align with today’s digital ecosystem. The research method includes Focus Group Discussions (FGDs) with 20 MSME actors to identify potential flagship products, followed by the development of a three-layer branding strategy: physical (packaging and logo), narrative (cultural storytelling), and digital (social media content and AI for market analysis and customer interaction). The results indicate a significant transformation in visual identity, a 67% increase in perceived product value, and expanded distribution channels from offline to online platforms. The targeted outcomes of this study include: a replicable village branding model based on local identity, improved digital literacy among MSME actors, and the development of a practical village branding guideline. These findings confirm that an integrated branding approach—combining local wisdom and appropriate technology—can serve as a sustainable strategy to counter the cultural homogenization driven by globalization. The success of the Cibungur Village branding model is expected to serve as a strategic reference for other rural MSME developments across Indonesia.